Conductas alimentarias y su relación con el estado nutricional en niños con autismo de 2 a 10 años, junta cantonal de protección de derecho cantón Babahoyo. Junio – octubre 2023. - Fuentes López, Nagelly Michelle (2023)
There is a relationship between the eating behaviors of children with autism and their nutritional status. Taking into account that the body mass index (BMI) is an important indicator to evaluate the nutritional status of children with autism, Autism is a neuropsychological disorder that usually appears at an early stage of life and persists until adulthood, with an increasing incidence. Increased intestinal permeability is associated with food hypersensitivity and allergies, and people with autism are very selective about their foods. All of this leads to nutritional deficiencies, which have serious consequences for the digestive system. The objective is to determine eating behaviors and their relationship with nutritional status in children with autism, taking into account that malnutrition is a common condition that can be prevented with adequate nutrition. In this investigative work, the descriptive method will be used, with this method the variables and the objective of the study will be recognized, through observation, description and analysis techniques. The incidence of nutritional status in children with autism, cared for by the cantonal board for the protection of rights of the city of Babahoyo in the period June - October 2023, according to the BMI, is 49% normal, 28% overweight, 13% obese, 8 % underweight, 2% malnutrition.